Edukasi Pemanfaatan Limbah Kulit Pisang sebagai Adsorben Limbah Zat Warna - Indri Susanti; Agus Santoso; Imroatul Hamidah (Cv. Utility Project Solution, 2023)
Banana peels are agricultural waste from bananas which are quite a lot in Moronyamplung Village, Kembangbahu District, Lamongan Regency. Banana peels waste contain functional groups that play a role in dye adsorption so that banana peels waste can be used as an adsorbent for dyes adsorption that contaminate water around Moronyamplung Village, Kembangbahu District, Lamongan Regency. The benefits and content of banana peels waste are the reason for conducting community service activities through educational activities with the aim the people of Moronyamplung Village, Kembangbahu District, Lamongan Regency can reuse banana peels waste which was previously just thrown away to become an absorbent material (adsorbent) for dyes. The results of community service show that there is an average increase in community understanding after education by the community service team. The increase in community understanding after calculating with N-Gain obtained a value of g = 0.62. The N-Gain value obtained is in the range of 0.3≤g≤0.7, which means that the increase in public understanding of educational activities has increased which is classified as moderate.